Sex, synchrony, and skin contact: integrating multiple behaviors to assess pathogen transmission risk. (20th February 2020) - Leu, Stephan T; Sah, Pratha; Krzyszczyk, Ewa; Jacoby, Ann-Marie; Mann, Janet; Bansal, Shweta
Abstract: Direct pathogen and parasite transmission is fundamentally driven by a population's contact network structure and its demographic composition and is further modulated by pathogen life-history traits. Importantly, populations are most often concurrently exposed to a suite of pathogens, which is rarely investigated, because contact networks are typically inferred from spatial proximity only. Here, we use 5 years of detailed observations of Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) that distinguish between four different types of social contact. We investigate how demography (sex and age) affects these different social behaviors. Three of the four social behaviors can be used as a proxy for understanding key routes of direct pathogen transmission (sexual contact, skin contact, and aerosol contact of respiratory vapor above the water surface). We quantify the demography-dependent network connectedness, representing the risk of exposure associated with the three pathogen transmission routes, and quantify coexposure risks and relate them to individual sociability. Our results suggest demography-driven disease risk in bottlenose dolphins, with males at greater risk than females, and transmission route-dependent implications for different age classes. We hypothesize that male alliance formation and the divergent reproductive strategies in males and females drive the demography-dependent connectedness and, hence, exposure risk to pathogens. Our study provides evidence for the risk of coexposure to pathogens transmitted along different transmission routes and that they relate to individual sociability. Hence, our results highlight the importance of a multibehavioral approach for a more complete understanding of the overall pathogen transmission risk in animal populations, as well as the cumulative costs of sociality. Abstract : Using contact networks, we show demographic effects on pathogen exposure risk. We investigate three different transmission routes (sexual, skin, and aerosol contact) in a dolphin population. We show that males are at greater risk than females and transmission route-dependent implications for different age classes. We determine the risk of coexposure and relate it to individual sociability. Our results highlight the importance of a multibehavioral approach to better understand the overall pathogen transmission risk in animal populations.